1882 Ill. Rev. Stat. 375 - (:unkn) unknown (My University, 1881)
§ 54(b): Prohibited selling, giving, loaning, hiring , bartering, or offering for sale any pistol, revolver, derringer, Bowie knife, dirk, or other deadly weapon to minors. Violators guilty of a misdemeanor, fined not less than twenty-five but no more than two hundred dollars.
Keywords: TRANSFER - MINORS